2022
DOI: 10.1039/d2en00050d
|View full text |Cite
|
Sign up to set email alerts
|

Simulated-sunlight-driven Cr(vi) reduction on a type-II heterostructured Sb2S3/CdS photocatalyst

Abstract: Photocatalysis technology is a promising strategy to solve the pollution of Cr(VI) wastewater. Transition metal sulfides (TMSs) are identified as a kind of important photocatalytic materials, but they are easy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Sampling and detecting the Cr(VI) concentration in a given time by diphenyl carbonate (DPC) spectrometry method. [ 13 ] Then, the Cr(VI) reduction photoactivities at different pH values were also investigated by adjusting the pH value of Cr(VI) aqueous solution. All the above experiments were repeated three times to obtain the corresponding error limits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling and detecting the Cr(VI) concentration in a given time by diphenyl carbonate (DPC) spectrometry method. [ 13 ] Then, the Cr(VI) reduction photoactivities at different pH values were also investigated by adjusting the pH value of Cr(VI) aqueous solution. All the above experiments were repeated three times to obtain the corresponding error limits.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Comparatively, cadmium sulfide (CdS) generally possesses high-performance photoactivity due to its suitable size and band structure. [12] In our previous study, [13] it was found that immobilizing CdS nanoparticles (NPs) on the surface of Sb 2 S 3 nanorods (NRs) can significantly improve the Cr(VI) reduction photoactivity. However, the very small contact area at the Sb 2 S 3 /CdS heterointerface led to weak interfacial interaction, resulting in unstable microstructure and limited promotion/suppression effect for separation/recombination kinetics of photoexcitons.…”
Section: Introductionmentioning
confidence: 99%
“…This was because that abundant H + could prevent catalyst from adsorbing Cr(VI), thereby hinder the efficient reduction of Cr(VI). [36,37]…”
Section: Evaluation Of Photocatalytic Activitiesmentioning
confidence: 99%
“…[3,4] Photocatalytic hydrogen production is an environmentally friendly and economical semi-catalytic reaction using solar energy to decompose water into hydrogen energy. [5,6] At present, the development of appropriate semiconductor materials to improve the utilization of photoelectrons is a major challenge for photocatalytic hydrogen production from water decomposition. This requires not only an appropriate decomposition band structure but also the requirements of high efficiency, low cost, and high stability as catalysts.…”
Section: Introductionmentioning
confidence: 99%